The book (Almuhamashun in Islamic History) by Dr. Mahmoud Ismail in Al-Mizan - Alsaeed, Khalid Abdullah (Journal of Humanities & Social Sciences, 2023)
The book (Almuhamashun in Islamic History) by well-known history professor Mahmoud Ismail Abdel Razek is considered one of the contemporary books that has gained some popularity among those interested in Islamic history. In this book, Dr. Mahmoud reviews a number of revolutions of the marginalized people - or the Muhamasheen as he called them - in different countries and throughout the hurricane, by employing material factors, economic and social, to understand the reality of these movements, explain their causes and analyze their results. Despite the novelty of the book's topic and the boldness of its idea, it did not escape many slips and falls. It is blamed on the author that he was always prejudiced against the rulers in power, biased towards the movements of the marginalized people, and fanatical towards the majority of jurists and historians, a position that is not based on an objective basis, as much as it expresses a personal whim he has.  Moreover, Dr. Mahmoud viewed the movements of the marginalized people through his socialist tendencies, which means his total reliance on material factors in interpreting the history of those movements in exchange for his marginalization of the rest of the other factors, such as religious ones, for example, which is a short reading that does not allow its owner to understand all the circumstances of those revolutions and its results. Because of his total bias towards the marginalized people in their revolutions, and his full commitment to the materialistic interpretation of history; Dr. Mahmoud was forced to elect what corresponds to his whim from the historical evidence in order to achieve his goals through open selectivity. These observations, and others that the reader will find when reading the research in detail, necessitate that he be careful and consider when reading such books whose authors claim that they are supporters of enlightenment and protectors of thought because their books may contain ideas aimed at distorting the image of Islamic history, dwarfing its achievements and exaggerating its mistakes.
Keywords: Almuhamashun in Islamic History; Mahmoud Ismail; marginalized people; revolutions; criticism